Pengaruh Media Modifikasi terhadap kemampuan Forehand Tenis meja pada Siswa Ekstrakurikuler di SDN I Ciawijapura - Siti Cahya Nursifa (Journal of Physical Education and Sport Science, 2022)
This study focuses on improving the forehand table tennis technique using a bouncing board at Extracurricular SDN I Ciawijapura. The purpose of this study was to determine the improvement of the forehand table tennis technique using a bouncing board for extracurricular students at SDN I Ciawijapura. The researcher used the bouncing board test instrument for 30 seconds (Nurhasan, 2001 : 164-167) to determine the improvement of the forehand technique using the bouncing board. The research method used is a quantitative method. One of the quantitative methods used in this research method is the experimental quantitative method with the research design used "One-Group Pretest-Posttest Design". Researchers have found that the forehand technique in the table tennis game using a bouncing board has increased, as evidenced by the significant value after being given treatment, namely using a modified bouncing board media, which increased by 3,715. The results of the hypothesis test also show that the value of tcount > ttable is (17.202 > 1.729) which means the hypothesis (Ha) is accepted.